Penguatan Sistem Pengelolaan Aset dan Inventaris pada Lembaga Pimpinan Wilayah Aisyiyah Jawa Barat - Pratiwi, Nurul Aziz; Minhajuddin, Minhajuddin; Putri , Kenny Nabila; Mukarom, Yogi (Jurnal SOLMA, 2025)
Background: Effective asset and inventory management is a key factor in improving efficiency and business sustainability, especially for small and medium-sized enterprises (SMEs). This activity aims to enhance the understanding and skills of SME entrepreneurs in managing their assets and inventories more effectively. Methods: The method used in this community service activity consisted of lectures and focus group discussions (FGD) on asset and inventory management in SMEs within the PWA (Pimpinan Wilayah Aisyiyah) Jawa Barat environment. The activity was attended by 25 participants from PWA Jawa Barat, students from the International Trade Program at UNISA Bandung, and special invited guests. Results: Through direct lectures and socialization, participants gained a better understanding of the importance of asset management, systematic record-keeping, and strategies to optimize inventory management to improve their business competitiveness. Participant understanding was evaluated through pre-test and post-test assessments, which showed a significant increase in awareness and comprehension after attending the activity. Conclusions: This community service activity (PkM) serves as an effort to assist women, particularly those from PWA Jawa Barat, in managing the assets and inventories of their SMEs. By doing so, they can maximize their business potential and sustainability.